STUDY ABOUT MAGNUS EFFECT ON SPINNING CYLINDERS AND ITS USE ON MICRO AIR VEHICLES - Stafy, Victor; Silveira Neto, Aristeu (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
It is described in this article a Magnus Effect research done on Magnus Effect on Spinning Cylinders and how the Drag and Lift varies as the Cylinder increase or decrease its tangential velocity, as other properties, vorticity and structures of the flow as well.The final objective of this study is to use a Spinning Cylinder, with success, instead of a wing as the component responsible for lift force on a Micro Air Vehicle, with this purpose in mind, some simulations were done in order to find the optimum cylinder for this application.The motivation of a study like that is to discover if it’s feasible the use of rotating cylinders on aircrafts that operates on low Reynolds numbers, which is the case of MAV’s. It was used as tool to obtain the results the CFD software STAR-CCM+®, to find the best cylinder configuration (more lift and less drag) based on the limitations of the project,several configurations were tested, varying the number of end-plates, the aspect ratio of the cylinder, and the Reynolds number of the plane through the mission.To be sure about the results of the simulations, a validation with experimental data was done, and a good agreement was met for the Î± (ratio between tangential velocity and the velocity of the flow) of interest to this research.